Pemanfaatan Media Belajar dalam Meningkatkan Prestasi Belajar Siswa - Hazmar, Al Afif; Hazmar, Rizqa; Marlian, Marlian (Asatiza: Jurnal Pendidikan, 2022)
This study aims to analyze how the use of learning media in relation to student achievement. Limited teaching resources, not all schools have source books, situations like this require teachers to learn illustration/visualization to provide available resources in the form of media. This type of research is library study, using the method of collecting data documentation by using books and journals as the main source. The data obtained are presented and analyzed so as to obtain interesting and scientific conclusions. The results of the study indicate that by utilizing various learning media can clarify students' knowledge, so that what is absorbed by the learner can be more profound and imprinted so that theoretically it will be able to affect student learning achievement.